Impact of lignin on water sorption properties of bioinspired self-assemblies of lignocellulosic polymers. (March 2015) - Muraille, L.; Pernes, M.; Habrant, A.; Serimaa, R.; Molinari, M.; Aguié-Béghin, V.; Chabbert, B.
Graphical abstract: Highlights: We design binary and ternary films of cellulose, hemicellulose and lignin. We examine the changes in water sorption properties with film composition. Synthesis of lignin in presence of hemicellulose give films with higher water sorption capacity. Cellulose modify water sorption properties of hemicellulose–lignin films. Abstract: The hygroscopic properties of lignocellulose-based films were investigated by designing bio-inspired nanostructured assemblies of increasing complexity. Binary and ternary films were prepared from three main secondary cell wall polymers, namely, cellulose, hemicellulose (xylan or glucomannan) and lignin. The effect of lignin was studied by varying the manner of lignin introduction as the dehydropolymer (DHP, model lignin). The infrared analysis and water-sorption properties of the films that resulted from mixing DHP and polysaccharides were compared with films obtained from the polymerisation of coniferyl alcohol (lignin monomer) in the presence of polysaccharides. Comparison of the film behaviours was achieved using the GAB and PARK models for the sorption isotherms and the PEK model for the sorption kinetics. Our data indicated that without chemical functionalization, the water-sorption properties of the hemicellulose films were enhanced after forming lignin under mild enzymatic conditions. Notably, the hydrophobic nature of lignin was not expressed in these films, in contrast to the systems that resulted from a simple mixing of lignin with hemicelluloses. The presence of cellulose also modified these sorption properties, most likely by altering the interactions between the polymers and/or the monolignol reactions.